An update on the management and outcomes of cancer patients with severe aortic stenosis. Issue 3 (14th December 2018) - Schechter, Michael; Balanescu, Dinu Valentin; Donisan, Teodora; Dayah, Tariq J.; Kar, Biswajit; Gregoric, Igor; Giza, Dana E.; Song, Juhee; Lopez‐Mattei, Juan; Kim, Peter; Balanescu, Serban Mihai; Cilingiroglu, Mehmet; et al.
Abstract: Objectives: We compared the outcomes of aortic valve replacement (AVR) by transcatheter (TAVR) and surgical (SAVR) routes with those of optimal medical management in patients with cancer and severe aortic stenosis (AS). Background: Cancer therapy requires optimal cardiac output; however, the treatment of AS in cancer patients is not established. Methods: Cancer patients with severe AS during January 2009 through February 2018 at a large cancer center were identified. Demographic and clinical characteristics including previous or active cancer diagnosis, history of chest radiotherapy, AS treatment, and survival were collected. Univariate Cox proportional hazards regression, the Kaplan–Meier analysis, and log‐rank tests were used to compare overall survival (OS) between AS treatment groups. Results: Sixty‐five cancer patients with severe AS were identified; 28 received optimal medical treatment alone, 30 received TAVR, and seven received SAVR. The patients were predominantly male (n = 44, 68%) with a mean age of 71.17 years. The median OS was 9.87 months, and the most common cause of death was cancer (n = 29, 94% of deaths). AVR was associated with a lower risk of death than no AVR (hazard ratio [HR] 0.38, P = 0.007), and patients who underwent TAVR (HR 0.36, P = 0.01) had better survival than those with no AVR. Malignancy type, stage, and treatment were not associated with OS. Conclusions: Patients with cancer and severe AS who underwent AVR, predominantly TAVR, experienced better survival than those who had no AVR regardless of cancer type or cancer treatment. TAVR may be considered in patients with cancer and AS.